The Function of Makyong Theater of "Cerita Putri Ratna" on Literature Learning in Senior High School - Anisah Kartika Putri; Suyitno Suyitno; Muhammad Rohmadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Study this aiming for describe the function from makyong theater is as Learning Literature in high school. This study uses descriptive methods qualitative to describe the phenomena that take place in the present and the past. The use of this type of research describes data with words or sentences that are distinguished according to certain parts of the elements to obtain conclusions. Data from this study are in the form of documents. The document used as a source of data in this study is a video of the performance of the makyong theater and the results of a document review from Malay royal library in the area of North Sumatra . The primary data sources in this study were (a) informants, (b) documents, (c)  Makyong Theater videos "Cerita Putri Ratna" . While secondary data sources are relevant primary books, international journals, papers, etc. that are needed in the study of theory. Data analysis used is an interactive analysis method. Based on the results of the study there are five main discussions, namely (1) Media Function of Aesthetic Expression, (2) Propaganda function, (3) education function.